Documentary Traces of Repression: A Methodological Approach to State Administrative Archives (Palimpsesto, 2025)
Based on a documentary survey conducted in the Historical General Archive of the Ministry of Foreign Affairs, this article proposes a methodological approach for analysing state administrative records produced during Chile's military dictatorship. The objective is to present how this methodology enabled the identification, examination, and connection of documentary traces that contribute to a deeper understanding of the functioning of the repressive system and the strategies used to persecute political opponents, both within the country and abroad.